Foot mycosis: clinical and epidemiological characterization in one referal center in Bogota, Colombia - Maria Sabogal (Asociación Colombiana de Infectología, 2019)
Objective: To describe the clinical and epidemiological characteristics of the population with cutaneous mycosis in the feet confirmed by positive mycological studies diagnosed in a reference center in Bogota, Colombia. Methods: Descriptive observational study in which all patients with lesions in the feet that were treated in the mycology service between 2011 and 2016 were included. In all cases KOH examination and fungal culture were performed. The sociodemographic and clinical characteristics, etiologies and the treatment profile were assessed using a bivariate analysis. Results: A total of 305 patients were included, of which 61% were men and 82% lived in an urban area of the city of Bogota. The most common behavior was to take a barefoot bath, the most important comorbidities were venous insufficiency and psoriasis, the main clinical form was interdigital and 35% of the cases presented simultaneously tinea pedis and onychomycosis. The group of dermatophytes was the most frequently isolated (95.2%). Discussion: Clinical examination corresponding with mycosis in the feet, direct examination, and positive culture, allow the physician accurate diagnosis and guide the most appropriate treatment of these infections according to their etiology. The sociodemographic characteristics of those who suffer from this mycosis in Colombia are related to their contagiousness and tendency to chronicity, therefore, the intervention of such aspects must be part of the strategies for their prevention